The Implementation of ICT-Based Materials and Metacognition Learning Strategy to Improve Studentsâ Vocabulary - Amraj, Akbar Kurtubi (Journal of ELT Research, 2018)
The purpose of this research is to find out the teachersâ and studentsâ perceptions on the implementation of ICT-based learning and metacognition to improve students vocabulary mastery at SMP (Junior Secondary School) Harapan Jaya II. This qualitative study applied a case study approach involving thirty eight students and one teacher as the participants. The data was collected through questionnaires, interviews and vocabulary test. The study revealed that the teacher had good perceptions about the implemented ICT-based materials, and the students showed motivation to learn English both in and outside the class. However, the teacher had the problem while in the classroom activity because the foundation of that school did not support the ICT-based learning. Therefore, he seldom used the projector in the class. Second,  based on the finding, the students had good perceptions to learn English using the ICT-based materials. 81.8% of students considered this strategy enjoyable. Third, the findings also indicated that there were some improvements of the studentsâ achievement on the vocabulary test. This is indicated by the improvement of the post test. Since the ICT-based learning and metacognition can improve the students vocabulary mastery, this research could be an alternative approach for English teacher to improve the studentsâ vocabulary. Keywords: ICT-based materials, metacognition learning strategy, and vocabulary mastery.